Experimental and theoretical researches of a resonator concept of a dielectric wakefield accelerator - Onishchenko, I.N.; Kiselev, V.A.; Linnik, A.F.; Onishchenko, N.I.; Sotnikov, G.V.; Uskov, V.V. (Вопросы атомной науки и техники, 2006)
Wakefield excitation in a cylindrical dielectric waveguide or resonator by a regular sequence of electron bunches
for application to high-gradient particle acceleration has been investigated theoretically and experimentally using an
electron linac «Almaz-2» (4.5 МeV, 6.103
bunches of duration 60 ps and charge 0.32 nC each). Исследовано возбуждение кильватерных полей в цилиндрическом диэлектрическом волноводе или резонаторе регулярной последовательностью электронных сгустков для целей высокоградиентного ускорения частиц как теоретически, так и в эксперименте на линейном электронном ускорителе «Алмаз-2» (4,5 МэВ, 6•103 сгустков длительностью 60 пс и зарядом 0,32 нКл каждый). Досліджено збудження кільватерних полів у циліндричному діелектричному хвилеводі або резонаторі регулярною послідовністю електронних згустків для цілей високоградієнтного прискорення часток як теоретично так і в експерименті на лінійному електронному прискорювачі «Алмаз-2» (4,5 МеВ, 6•103 згустків тривалістю 60 пс і зарядом 0,32 нКл кожний).